Descriptions of Wolf Attacks on Bison Calves in Wood Buffalo National Park - Carbyn, L.N.; Trottier, T. (ARCTIC, 1988)
Wolf predation on bison in Wood Buffalo Park and adjacent areas in late spring/early summer season was observed to be directed toward cow/calf herds. While hunting, wolf packs in early summer developed a strong preference for herds with calves. Packs of four to six individuals were observed. Of 14 interactions recorded, 12 were made from ground observations and 2 were made from the air. Five apparent defense strategies to protect calves were noted. These were: (1) to run to the cow, (2) to run to a herd, (3 ) to run to the nearest bull, (4) to get out in front and center of a stampeding herd and (5) to run through water bodies. When fleeing from wolves in open areas, cow with young calves took the lead, while bulls often were seen at the rear of the herds. When under attack from wolves, cows and particularly bulls were sometimes seen to defend the calves. Killing attempts observed in this study lasted from a few minutes to 11 hours.Key words: wolf predation, bison, wolves, antipredator defense, Wood Buffalo National Park Mots clés: prédation des loups, bisons, loups, défense contre les prédateurs, parc national Wood Buffalo